DBU-catalyzed biobased poly(ethylene 2, 5-furandicarboxylate) polyester with rapid melt crystallization: synthesis, crystallization kinetics and melting behavior. Issue 103 (25th October 2016) - Wu, Jiaping; Xie, Hongzhou; Wu, Linbo; Li, Bo-Geng; Dubois, Philippe
Abstract : PEF synthesized by non-metallic catalyst (DBU) exhibited rapid melt crystallization in both non-isothermal and isothermal conditions. Abstract : Poly(ethylene 2, 5-furandicarboxylate) (PEF) is in the spotlight as a new emerging biobased polyester. Usually, PEF exhibits very slow and weak melt crystallization behavior. In this study, PEF synthesis via a transesterification polycondensation method catalyzed by 1, 8-diazabicyclo[5.4.0]undec-7-ene (DBU) as an organic nonmetallic catalyst was attempted. PEF with a moderate molecular weight (intrinsic viscosity 0.54 dL g −1 ) and low diethylene glycol furandicarboxylate unit content (DEGF 1.7%) was successfully synthesized and the melt crystallization kinetics and melting behavior were investigated. The DBU-catalyzed PEF exhibited rapid melt crystallization in both nonisothermal and isothermal manners. At cooling rate of 10 °C min −1, a melt crystallization peak appeared around 158 °C with a crystallization enthalpy of 29 J g −1 . DSC and WAXD results indicated a crystallinity of 27–34% after sufficient isothermal melt crystallization at 160–210 °C. A minimum of melt crystallization half time, 1.6 min, appeared at 160 °C. The equilibrium melting point of PEF was estimated to be 243 °C.